Analysis of Digital Competencies of 21st Century Teachers of Mathematics Education by Pentagonal Fuzzy Number and Some of Its Arithmetic Operations - Rahul Kar; Ashok Kumar Shaw (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
Digital competencies is a collection of digital skills, categorized into five main areas of focus. They are designed as a tool for students to use to reflect on the digital skills and critical perspectives they develop while in school or college, in curricular and co-curricular experiences. The factors in digital competencies are digital survival skills, digital communication, data management and preservation, data analysis and presentation, critical making, design and development. In this paper we use pentagonal fuzzy number to find out the failure of digital competencies of 21st century teacher in mathematics education on the basis of the above criteria.